State versus action orientation and compliance during the COVID-19 pandemic in Indonesia - Andrie Elia; Danes Jaya Negara; Ferdinand; Sunaryo Neneng; Meitiana; Trecy Anden; Maria Haryulin Astuti; Hendrik Segah (Heliyon, 2022)
This study explored the roles of activity versus state direction in how Indonesians adhered to COVID-19 preventive behaviour using the theory of planned behaviour (TPB). A total of 615 participants were gathered through a web questionnaire containing 68 questions. Structural equation modelling (SEM) was used to determine the causal relationships of the latent variable construct. The results revealed that information sources positively influence both attitudes and subjective norms toward preventive behaviour. The results also support self-regulation as a moderator of the main intent-behaviour relationship. Moreover, state-oriented people cannot self-regulate their behaviour to comply with COVID-19 protocols. This investigation provides productive experiences for strategists and managers to improve COVID-19 compliance. This paper's analysis also contributes to literature by revealing the intention to comply with COVID-19 protocols by emphasizing the role of self-regulation. The findings are relevant to practitioners and policymakers in the field of public health and managing of human behavior, particularly to improve of compliance with COVID-19 prevention. Therefore, governments or public health organizations can be utilized to improve the number of individuals who practice COVID-19 preventative behaviours now and in the future, but various factors must be addressed. Future directions and recommendations for improving TPB are suggested.